Cytotoxic effects of Lavandula angustifolia seed extracts on the viability of Huh-7 and Chang liver cells - Alshammari, Ghedeir M. (PLOS ONE, 2022)
Flowering plants are valuable in numerous ways, including food/feed supply for living organisms, fuel production, and medicinal uses. Several plant extracts/products are used to treat variety of serious ailments in human and animals. Lavandula angustifolia is a flowering plant that possesses anti-inflammatory and anti-depressive medicinal properties. Cancer is a deadly disorder affecting millions of people globally. It affects several human organs, including liver, stomach, and lungs. Several researchers are doing efforts to eliminate the disease around the globe. In this study, Chang and Huh-7 liver cell lines were utilized as human normal hepatocyte model and innovation to mimic the liver environment. Cytotoxicity of L. angustifolia seed extracts was investigated at two different concentrations (50% and 100%) against Chang and Huh-7 liver cell lines by colorimetric assay which is used to assess cell metabolic activities. The Chang and Huh-7 liver cell lines were treated with L. angustifolia seeds extracts (50% and 100%) and incubated for 24 and 48 hours under standard conditions (37°C, 5% CO2). The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was employed to quantify cell survival. Seed extracts of L. angustifolia exerted varied cytotoxic effects depending on the concentration and treatment duration. The results indicated that L. angustifolia seed extracts with 100% concentration exhibited the highest cytotoxicity against Huh-7 and Chang liver cell lines. In conclusion, L. angustifolia seed extracts exhibited cytotoxic activity which can be enhanced based on the concentration and treatment duration. The findings of the current study are critical for the development of novel herbal-based therapies for fatal disorders such as liver cancer. However, more investigations are required to reveal cytotoxicity mechanisms of L. angustifolia seed extracts.